Pengaruh Kualitas Informasi, Kualitas Sistem, dan Kualitas Layanan Terhadap Minat Beli Ulang Pengguna E-Commerce Situs Blibli.Com dengan Kepuasan Sebagai Variabel Intervening pada Masyarakat Kota Padang - Deri Rahma Yandi; Whyosi Septrizola (Universitas Negeri Padang, 2019)
Purpose - This study analyses: (1) The effect of the quality of information on satisfaction (2) the effect of system quality on satisfaction (3) the effect of service quality on satisfaction (4) the effect of satisfaction on repurchase intention. (5) the effect of information quality on re-purchase intention trought satisfaction as an intervening variable (6) the effect of system quality on repurchase intention trought satisfaction as an intervening variable (7) the effect of service quality on repurchase intention trought satisfaction as an intervening variableMethodology - This type of research is causative research. The population in this study were consumers who had used Blibli.com in the city of Padang, whose numbers were unknown. By using purposive sampling we use 230 correspondents. This study used an online questionnaire as an instrument for data collection. This study analyzed data using structural equation modeling (SEM) with PLS 3.0 software packages.Finding - The results of his study indicate that: (1) Information quality has a significant effect on satisfaction (2) System quality have a significant effect on satisfaction (3) Service quality have a significant effect on satisfaction (4) Satisfaction have a significant effect on repurchase intention (5) Information quality has a significant effect on repurchase intention trought satisfaction as an intervening variable (6) System quality have a significant effect on repurchase intention trought satisfaction as an intervening variable (7) Service quality has a significant effect on repurchase intention trought satisfaction as an intervening variable. Keywords: Repurchase intention, satisfaction, service quality, system quality, information quality.